PENGARUH STATUS SOSIAL EKONOMI KELUARGA DAN MOTIVASI BELAJAR TERHADAP KREATIVITAS BELAJAR SISWA - Ganita Saldan; Ade Rustiana; Rendra Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem of this research is the low creativity of students. The purpose of this study was to find out how the influence of family socio-economic status and learning motivation on learning creativity. The research method used is a survey method with a quantitative approach. The population in this study were all students of class XI IPS SMA Negeri 4 Tasikmalaya City, totaling 214 students. The sampling technique is non-probability sampling, namely by saturated sampling, the selection of saturated samples is that all populations are used as samples, namely 214. The data collection technique in this study is to use a questionnaire with multiple linear regression analysis techniques. The results showed that the socio-economic status of the family had a significant effect on learning creativity in class XI IPS students at SMA Negeri 4 Tasikmalaya City, learning motivation had a significant effect on learning creativity in class XI IPS students at SMA Negeri 4 Tasikmalaya City. Family socio-economic status and learning motivation on learning creativity have a significant effect on economic learning achievement in class XI IPS students of SMA Negeri 4 Tasikmalaya City with a significance value of 0.001 <0.05